2019
DOI: 10.3390/s19030536
|View full text |Cite
|
Sign up to set email alerts
|

Fully Integrated Light-Sensing Stimulator Design for Subretinal Implants

Abstract: This paper presents a fully integrated photodiode-based low-power and low-mismatch stimulator for a subretinal prosthesis. It is known that a subretinal prosthesis achieves 1600-pixel stimulators on a limited single-chip area that is implanted beneath the bipolar cell layer. However, the high-density pixels cause high power dissipation during stimulation and high fabrication costs because of special process technologies such as the complementary metal-oxide semiconductor CMOS image sensor process. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The output of the LDO provides a positive supply voltage to 64 pixels stimulator circuit which requires maximum current of 10 mA. This requirement is based on our previous work which can be found in [10]. In the experimental setup to evaluate the line-transient responses of LDO, a 100 Ω resistor was chosen as a load for the LDO output terminal so that the load current is larger than 10 mA.…”
Section: Simulation and Measurement Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The output of the LDO provides a positive supply voltage to 64 pixels stimulator circuit which requires maximum current of 10 mA. This requirement is based on our previous work which can be found in [10]. In the experimental setup to evaluate the line-transient responses of LDO, a 100 Ω resistor was chosen as a load for the LDO output terminal so that the load current is larger than 10 mA.…”
Section: Simulation and Measurement Resultsmentioning
confidence: 99%
“…The command data modulated on the RF carrier are recovered using the demodulator and sent to the global digital controller that decodes the demodulated data in order to activate the stimulator array. Here, a single-pixel stimulator, which is composed of a photosensor, current amplifier, and pulse shaper [10], generates a biphasic current pulse, which is delivered to the bipolar cells through a microelectrode. Back telemetry is utilized to observe the operating status of the implanted device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially applicable in patients with blindness due to photoreceptor necrosis, where electrodes can be implanted in the retina to effectively stimulate bipolar or ganglion cells and subsequently enhance visual signal transmission. A retinal prosthesis chip is comprised of three structural units: a photodiode array, a photosensor with current amplifiers, and a biphasic circuit [38]. The power is mainly supplied by photovoltaic batteries, which convert incident light into electrical energy.…”
Section: Application Of Retinal Prosthesismentioning
confidence: 99%
“…There is a long-lasting effort to increase the resolution and visual acuity of retinal implant [6,18,19]. Previous simulation has shown that a super-high density of 600–1000 stimulus electrodes (pixels) is required to help blind people with face recognition and reading large text in newspapers [20].…”
Section: Introductionmentioning
confidence: 99%